Biomechanical Comparison of A Novel Dynamic Cervical Implant With Conventional Implant: A Finite Element Study. Issue 1 (February 2021) - Samanta, S; Paul, T; Mondal, D; Biswas, Dr. J K
Abstract: Ball-socket pair is generally used for designing implants for total disk replacement (TDR) surgery on cervical spine. Although, there is exists an issue of wear which reduces implant's life as well as success rate. To overcome this issue, without compromising stability, a new design of dynamic cervical implant (DCI) is introduced. In this present study, biomechanical performances of a conventional Prodisc-C and the proposed DCI were compared using finite element (FE) analysis. CT scan data was used to develop three-dimensional model of cervical spine (C4–C7), and the implants were inserted at C5-C6 segment. The FE model with Prodisc-C showed an increase in range of motion (ROM) at the implanted segment and decrease in adjacent segment, while the proposed DCI design showed convenient results in term of ROM compared to intact spine model, and lower risk of stress shielding at the adjacent bone.